A simple sarcopenia screening test predicts future adverse events in patients with heart failure. (15th July 2016) - Onoue, Yoshiro; Izumiya, Yasuhiro; Hanatani, Shinsuke; Tanaka, Tomoko; Yamamura, Satoru; Kimura, Yuichi; Araki, Satoshi; Sakamoto, Kenji; Tsujita, Kenichi; Yamamoto, Eiichiro; Yamamuro, Megumi; Kojima, Sunao; et al.
Abstract: Background: Progressive loss of skeletal muscle termed "sarcopenia" is an independent risk factor for mortality in patients with cardiovascular diseases. A simple screening test that can identify sarcopenia using three variables (age, grip strength and calf circumference) was recently developed. We evaluated the clinical utility of this screening test in patients with heart failure (HF). Methods and results: HF patients were divided into the sarcopenia (n = 82) and non-sarcopenia (n = 37) groups based on the sarcopenia score. Circulating BNP and high-sensitive cardiac troponin T levels were significantly higher, and left ventricular ejection fraction was lower in the sarcopenia group than non-sarcopenia group. Kaplan–Meier curve showed that HF event-free survival rate was significantly lower in the sarcopenia group. Multivariate Cox proportional hazards analysis identified BNP (ln[BNP]) (hazard ratio [HR]: 1.58; 95% CI: 1.09–2.29, p = 0.02), hs-CRP (ln[CRP]) (HR: 1.82; 95% CI: 1.23–2.68; p < 0.01) and sarcopenia score (HR: 1.03; 95% CI: 1.01–1.05, p < 0.01) as independent predictors of HF events. In receiver operating characteristic analysis, adding the sarcopenia score to BNP levels increased an area under the curve for future HF events (sarcopenia score alone, 0.77; BNP alone, 0.82; combination, 0.89). Conclusions: The sarcopenia screening test can be used to predict future adverse events in patients with HF.